2016
DOI: 10.3389/fpsyg.2016.01198
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Bi-Lingual Assessment Instrument to Measure Agentic and Communal Consumer Motives in English and French

Abstract: Consumer behavior is driven, in part, by the degree to which goods and services appeal to underlying motives for agency and communion. The purpose of this research was to develop a brief individual differences measure of these motivations for use in behavioral research and theoretical and applied consumer psychology and marketing studies. We employed a bi-lingual scale development procedure to create the 10-item Agentic and Communal Consumer Motivation Inventory (ACCMI) in English and French. Two studies show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This and the SCM context effects (relational vs. analytic; Nicolas et al, 2021) thus argue for adding a congruence (fit) principle to the BIAF. In order to help managers make informed decisions about which dimensions to put forward, a scale measuring agentic and communal consumer motives has since developed (Friedman et al, 2016).…”
Section: Replications and Developments Of The Brands As Intentional Agents Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This and the SCM context effects (relational vs. analytic; Nicolas et al, 2021) thus argue for adding a congruence (fit) principle to the BIAF. In order to help managers make informed decisions about which dimensions to put forward, a scale measuring agentic and communal consumer motives has since developed (Friedman et al, 2016).…”
Section: Replications and Developments Of The Brands As Intentional Agents Frameworkmentioning
confidence: 99%
“…This and the SCM context effects (relational vs. analytic; Nicolas et al, 2021) thus argue for adding a congruence (fit) principle to the BIAF. In order to help managers make informed decisions about which dimensions to put forward, a scale measuring agentic and communal consumer motives has since developed (Friedman et al, 2016). This congruence principle does indeed provide a useful tool to interpret other research that has found varying importance of warmth versus competence in their impact on consumer attitudes and behaviors.…”
Section: Congruence Effectmentioning
confidence: 99%